Evidence of co-production in public service provision: the case of the administrative arbitration centre in Portugal - Silvestre, Hugo Marco Consciência (2016)
Co-production includes all actions where citizens assist, as volunteers, in the provision of services by public agencies in order to increase theefficiency and efficacy of the public services provided. This practice, known as co-production, is being adopted by governments in the resolutionof conflicts, particularly those regarding administrative and fiscal matters. However, is co-production a more efficient and effective way of settlingdisputes in administrative and tax areas than the traditional administrative model? And why? In Portugal, the Administrative Arbitration Centrewas created in 2009 with the aim of resolving disputes between public administration and taxpayers/service users by means of co-production. Theavailable data support the thesis that efficiency and efficacy are higher under the co-production model. Nevertheless, users are not totally satisfiedsince the costs associated with the use of this service provision model are also higher.